Neckties and Cerebrovascular Reactivity in Young Healthy Males: A Pilot Randomised Crossover Trial - Mark Rafferty; Terence J. Quinn; Jesse Dawson; Matthew Walters (Stroke Research and Treatment)
Background. A necktie may elevate intracranial pressure through compression of venous return. We hypothesised that a tight necktie would deleteriously alter cerebrovascular reactivity. Materials and Methods. A necktie was simulated using bespoke apparatus comprising pneumatic inner-tube with aneroid pressure-gauge. Using a randomised crossover design, cerebrovascular reactivity was measured with the “pseudo-tie” worn inflated or deflated for 5 minutes (simulating tight/loose necktie resp.). Reactivity was calculated using breath hold index (BHI) and paired “t” testing used for comparative analysis. Results. We enrolled 40 healthy male volunteers. There was a reduction in cerebrovascular reactivity of 0.23 units with “tight” pseudotie (BHI loose 1.44 (SD 0.48); BHI tight 1.21 (SD 0.38) P<.001). Conclusion. Impairment in cerebrovascular reactivity was found with inflated pseudo-tie. However, mean BHI is still within a range of considered normal. The situation may differ in patients with vascular risk factors, and confirmatory work is recommended.